Structural Modification of Magnetic Properties in Perpendicularly Magnetized Co/Pd Multilayer for M RAM - Budi Purnama (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
The structural modification of magnetic properties in as grown films of Co/Pd multilayer with perpendicular magnetic anisotropy (PMA) has been systematically studied. The thickness dependence of element multilayer for both the Co thickness tCo and the Pd thickness tPd as parameters was investigated. Occurred PMA should be correlated to between bi-layers and following the enhancement of interface interaction due to the increase of repetition number bi-layers. The optimal experimental result was obtained for Co = 1.7 Å and Pd = 8.0 Å realizing very good square shape hysteresis curve and high coercive field Hc of 1.5 kOe.